The Role of Academic Background in English Private Tutors’ Language Proficiency - Wibowo, Raihana Tsabita; Nugroho, Him'mawan Adi; Munir, Ahmad (Universitas Pahlawan Tuanku Tambusai, 2025)
Private English tutoring in Indonesia has become popular due to student demand. In practice, English private tutors mostly graduated from a linear academic background, whether in the English language and literature or education study program. English tutors who graduated from non-linear study programs have the same opportunity to teach English and perform their language-ability. This present study applied narrative inquiry to know how the private tutors’ academic background and learning journey outside formal education shaped their English proficiency. The participants of this study are four private English tutors; two tutors graduated from the English language and education, and the other two graduated from political science, who have been teaching for more than two years and achieved more than 500 scores in their TOEFL. The findings reveal that the tutors’ non-linear academic background and personal life experiences also helped how they could practice their communication skills using English.